Special cardfiles of “Political shades“ in Estonia in 1940–1957 - Rahi-Tamm , Aigi (Genocidas ir rezistencija, 2006)
The Baltic states, occupied and annexed by the Soviet Union, had to be incorporated into the common political system of the USSR without delay. The Soviet model was to be used to create a repressive apparatus and a political violence against the local populations that was directly linked to it. The archives of the NKVD played a certain role in this process. To purge society of 'foreign elements', the security organs needed compromising material. This was sought in the archives. A seamless system for collecting such data was established and launched in the Soviet Union in September 1939. The archives were obliged to keep and maintain a filing system of all political stripes. This filing system was union–wide, initially covering 27 individual categories of persons of all political stripes. Who was included in the filing system of all political stripes in Estonia in 1940? First on the list were former members of the Government of the Republic of Estonia, employees of the courts, prosecution and administrative bodies, party members, policemen and military officers. Over the years, the ranks of suspicious persons have increased significantly. The work on the filing system of all political stripes was discontinued in 1957, but similar individual files continued to be filed in the archives well into the 1960s and beyond, even until 1989.
Keywords: Estonia; repressive structures; repressions; archive